2020
DOI: 10.3389/fmicb.2020.01676
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Respiratory Syncytial Virus Enhances the Adherence of Pasteurella multocida to Bovine Lower Respiratory Tract Epithelial Cells by Upregulating the Platelet-Activating Factor Receptor

Abstract: Coinfection by bovine respiratory syncytial virus (BRSV) and Pasteurella multocida (PM) frequently has been observed in cattle that develop severe pneumonia. We recently reported that BRSV infection significantly increased PM adherence to bovine lower respiratory tract epithelial cells. However, the molecular mechanisms of enhanced PM adherence are not completely understood. To investigate whether BRSV infection regulates any cellular adherence receptors on bovine bronchus-and lung-epithelial cells, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We recently demonstrated that expression of two cell surface receptors, platelet-activating factor receptor (PAF-R) and intercellular adhesion molecule-1 (ICAM-1), determines the adherence of PM to BRSV-infected BRECs ( Sudaryatma et al, 2020a , 2020b ). Based on this finding, we measured the expression levels of these receptors by qRT-PCR and western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that expression of two cell surface receptors, platelet-activating factor receptor (PAF-R) and intercellular adhesion molecule-1 (ICAM-1), determines the adherence of PM to BRSV-infected BRECs ( Sudaryatma et al, 2020a , 2020b ). Based on this finding, we measured the expression levels of these receptors by qRT-PCR and western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the number of adhering bacteria decreased and increased in BRSV-infected cells derived from the upper and lower respiratory tract, respectively. These changes in the number of adhering bacteria were caused by down- and upregulation, respectively, of two bacterial adhesion molecules ( Sudaryatma et al, 2020a , 2020b ). Reduced and enhanced bacterial adherence to BRSV-infected upper and lower BRECs would permit bacteria to pass from the upper to lower respiratory tract, inducing severe pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of viruses in the bovine respiratory tract may also alter the microenvironment of mucosal surfaces and bacterial structure, leading to reduced mucociliary function and cilia damage. Additionally, viral infection could reduce the concentration of antimicrobial peptides, bacterial adherence and invasion by adjusting the host immune system [ 129 ]. Segal et al [ 130 ] observed that enhanced expression of inflammatory cytokines (Th17 immune activation) is associated with bacteria in the human LRT, which indicates that the respiratory microbiota could regulate the inflammatory condition at the mucosal surface in humans.…”
Section: Association Between the Respiratory Microbiome And Brdmentioning
confidence: 99%
“…The authors noticed that P. multocida adherence was greatly increased in pre-infected cells derived from the lower respiratory tract compared to cells that were not previously exposed to BRSV, together with an up-regulation of IL-6 mRNA expression. The same authors later reported an increased accumulation of the platelet-activating factor receptor (PAFR) in vitro and also demonstrated that P. multocida adherence depended on PAFR expression [ 133 ]. This work highlights a possible mechanism of bacterial superinfection caused by P. multocida following BRSV infection, that is often observed in field conditions [ 8 ].…”
Section: Impact Of Coinfections On Respiratory Pathology In Cattle: W...mentioning
confidence: 99%